The Alignment Of Auditing Practice With International Standards - Aida ,Anouar (جامعة الوادي University of Eloued, 2025)
This study aimed to investigate the current state of the auditing profession and its practical procedures within the Algerian context, as well as to compare Algerian auditing standards with international ones. To achieve these objectives, the study analyzed data collected from a questionnaire distributed to a sample of auditors. Findings indicate that international auditing standards are widely accepted among Algerian professionals and stakeholders. The auditing profession was found to serve multiple beneficiaries of financial statements, and the adoption of international standards is expected to enhance the credibility of financial statements for foreign investors. The study recommends the implementation of specialized auditor training programs focused on applying international auditing standards.
The Alignment of Auditing Practice with International Standards: A Field Study in the Algerian Context
Keywords: Auditor; International Auditing and Standards; Auditing